Mahzab Sunan Kalijaga (Refleksi Setengah Abad Genealogi Epistemologi Studi Ilmu Hukum Islam Integratif di Fakultas Syari’ah dan Hukum UIN Sunan Kalijaga: 1963-2013) - Riyanto, Waryani Fajar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
The title above, exactly as the title of the book that has been prepared by the writer to welcome half century (50 years) of the age of Faculty of Syari’ah and Law UIN Sunan Kalijaga: 1963-2013, which may God willing, will be launched in the middle of 2014. Here the author deliberately uses the term “Mazhab Sunan Kalijaga“, to summarize the four types of epistemology nodes that have ever been flourished in the FSH, namely: Indonesian Fiqh, Indonesianizing of Indonesian Fiqh, Mazhab Jogja, and Integration-Interconnection. By the historical, critical, and analytical approaches, this initial study is expected to provide enlightenment and the making smart effort of history for FSH.